2007
DOI: 10.1073/pnas.0706609105
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic H-Ras V12 promotes anchorage-independent cytokinesis in human fibroblasts

Abstract: Cell anchorage is required for cell proliferation of untransformed cells, whereas anchorage-independent growth can be induced by oncogenes and is a hallmark of transformation. Whereas anchorage-dependent control of the progression of the G1 phase of the cell cycle has been extensively studied, it is less clear whether and how anchorage may control other cell cycle phases and whether oncogenes may affect such controls. Here, we found that lack of cell anchorage did not influence progression through the cell cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(65 citation statements)
references
References 40 publications
(47 reference statements)
3
61
1
Order By: Relevance
“…One might imagine, therefore, that when placed in a non-adhesive environment, cells might face difficulties in division. This is indeed the case for human fibroblasts, which when entering mitosis in suspension, suffer a critical failure in cytokinesis, an effect that can be rescued by transformation with oncogenic Ras [11].…”
Section: The Division Of Metastatic Cancer Cells In Novel Environmentsmentioning
confidence: 87%
See 1 more Smart Citation
“…One might imagine, therefore, that when placed in a non-adhesive environment, cells might face difficulties in division. This is indeed the case for human fibroblasts, which when entering mitosis in suspension, suffer a critical failure in cytokinesis, an effect that can be rescued by transformation with oncogenic Ras [11].…”
Section: The Division Of Metastatic Cancer Cells In Novel Environmentsmentioning
confidence: 87%
“…Moreover, circulating tumor cells have been reported to express proliferation markers [13]. Then, in order to form metastases, cells must undergo a process of extravasation to leave the blood/lymphatic system to colonize a new tissue environment, where they must proliferate despite differences in matrix composition and mechanics compared with their tissue of origin.microenvironment affect spindle positioning and division [7][8][9][10][11] it is likely that mitosis in a foreign environment presents a challenge. This may explain, in part, why metastasized cells often initially enter a dormant non-proliferative phase when introduced to a new environment [12].…”
Section: The Division Of Metastatic Cancer Cells In Novel Environmentsmentioning
confidence: 99%
“…28 In contrary, we found that human primary fibroblasts progressed through mitosis until cytokinesis when cultured without anchorage, and that the tubulin spindles were still formed and sister chromatids separated in suspension. 25 Further, the central spindle was formed and contained tubulin, Aurora B and Rho A similar to the anchored cells , and also the midbody was formed in primary human fibroblasts cultured in suspension. 25 Importantly, lack of anchorage appears to play a role during cytokinesis, since several studies published almost 30 years ago described the formation of bi-nucleated cells caused by culture without proper substratum.…”
Section: Dual Periods Of Regulation Of Anchorage-dependent Cell Divisionmentioning
confidence: 96%
“…However, human primary fibroblasts progress perfectly through the S-and G 2 -phases without anchorage. 25 Nevertheless, it may be indicated from visual inspection that anchoring proteins and cytoskeleton remodeling might regulate some of the stages during mitosis. Onset of mitosis coincide with cellular de-adhesion and actin cytoskeleton remodeling inducing cell rounding that is prominent during prometaphaseanaphase (Fig.…”
Section: Dual Periods Of Regulation Of Anchorage-dependent Cell Divisionmentioning
confidence: 99%
See 1 more Smart Citation